Harmonisation of the HLA tests for the diagnosis of coeliac disease: experiences from the Czech external proficiency testing program - Vrana, Milena; Tajtlova, Jana; Mrazek, Frantisek (Frontiers in Genetics, 2024)
Coeliac disease (CD) is an autoimmune disorder caused by the ingestion of gluten-containing grains. One of the prerequisites for the development of the disease is the presence of specific combinations of HLA alleles at the DQA1 and DQB1 loci. The HLA test is a supportive examination for the diagnosis. In the Czech Republic, about 3500 of HLA tests for CD diagnostics are performed annually in almost three dozen of the laboratories. The HLA Department of the Institute of Hematology and Blood Transfusion in Prague has been offering EPT "Detection of HLA Alleles Associated with Diseases" for more than ten years. The results are evaluated in terms of correct determination of predisposing alleles/allelic groups and the clinical interpretation. Every year we notice some problems with the detection of CDassociated alleles and the interpretation of the results. Annual workshops are part of this EPT and they concern also on recommendations for result interpretation. The interpretation is evolving based on current knowledge in the field. The current recommendation for interpretation was adopted in 2023. This recommendation divides HLA-DQA1/DQB1 genotypes into three categories:Detected HLA genotype is associated with predisposition to coeliac disease 2) Coeliac disease could not be excluded based on detected HLA genotype.Coeliac disease could be excluded with high probability based on detected HLA genotype.The quality of examinations is increasing but still has to be improved. Correct results and accurate interpretation can help clinicians to concern on diagnosis of coeliac disease in appropriate patients.